The Pythagorean Theorem: II. The infinite discrete case - Kadison, Richard V. (National Academy of Sciences, 2002)
The study of the Pythagorean Theorem and variants of it as the basic result of noncommutative, metric, Euclidean Geometry is continued. The emphasis in the present article is the case of infinite discrete dimensionality.